2006
DOI: 10.1089/clo.2006.8.295
|View full text |Cite
|
Sign up to set email alerts
|

Zygotically Activated Genes Are Suppressed in Mouse Nuclear Transferred Embryos

Abstract: Mammalian oocytes have the ability to confer totipotency to terminally differentiated somatic cell nuclei. Viable cloned animals have been produced by somatic cell nuclear transfer (NT) into oocytes in many mammalian species including mouse. However, the success rates of the production were quite low in all species. Many studies have measured differences in gene expression between NT and fertilized embryos in relatively advanced stages of development such as pre- and post-natal stages or the blastocyst stage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 64 publications
1
29
0
1
Order By: Relevance
“…Transcription of this gene begins as early as the 1-cell stage, continues through the early 2-cell stage, and is repressed coincident with the second round of DNA replication [38]. The expression patterns of three other genes, MuERV-L, U2afbp-rs, eIF-1A and some of the genes recently identified in our study described below are similar to the transient expression pattern of Hsp70.1 during ZGA [26,[48][49][50]. The expression of Xist has also been reported to begin during ZGA [51].…”
Section: Genes Transcribed During Zygotic Gene Activationsupporting
confidence: 65%
“…Transcription of this gene begins as early as the 1-cell stage, continues through the early 2-cell stage, and is repressed coincident with the second round of DNA replication [38]. The expression patterns of three other genes, MuERV-L, U2afbp-rs, eIF-1A and some of the genes recently identified in our study described below are similar to the transient expression pattern of Hsp70.1 during ZGA [26,[48][49][50]. The expression of Xist has also been reported to begin during ZGA [51].…”
Section: Genes Transcribed During Zygotic Gene Activationsupporting
confidence: 65%
“…In addition, it has been reported that rRNA plays an important role in cell proliferation [13]. The reduced production of mature rRNA detected in this study may explain the low cell numbers in mouse NT blastocysts [25,36].…”
Section: Discussionmentioning
confidence: 48%
“…Based on the reports that most NT embryos cease development at the pre-and peri-implantation stages [1,41], it is probable that the accumulation of different abnormalities observed in NT embryos at various developmental stages, such as failure to erase some of the features of donor cells [42][43][44], abnormal gene expression [4,8,10,25,[45][46][47], abnormal DNA methylation [4][5][6], abnormal formation of placentae [1,41,[48][49][50], and the abnormalities detected in this study, leads to gradual loss of NT embryos. Abnormalities that have not been detected in previous studies and/or small differences in gene expression may seriously affect embryonic development.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations